Charge-Trapping Non-Volatile Memories Volume 2--Emerging Materials and Structures - Dimitrakis, Panagiotis; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book describes the technology of charge-trapping non-volatile memories and their uses. The authors explain the device physics of each device architecture and provide a concrete description of the materials involved and the fundamental properties of the technology. Modern material properties, used as charge-trapping layers, for new applications are introduced. Provides a comprehensive overview of the technology for charge-trapping non-volatile memories; Details new architectures and current modeling concepts for non-volatile memory devices; Focuses on conduction through multi-layer gatedielectrics stacks.
Materials and Device Reliability in SONOS Memories -- Charge-Trap-Non-Volatile Memory and Focus on Flexible Flash Memory Devices -- Hybrid Memories Based on Redox Molecules -- Organic Floating-Gate Memory Structures -- Nanoparticles Based Flash-like Non Volatile Memories: Cluster Beam Synthesis of Metallic Nanoparticles and Challenges for the Overlying Control Oxide Layer.
Keywords: Nanotechnology; Electronic circuits; Electronics; Computer storage devices; Memory management (Computer science).; Materials; Nanotechnology; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation; Computer Memory Structure; Materials Engineering